Tahap Perkembangan Mikrospora pada Solanum melongena L. - Devi Bunga Pagalla (Universitas Muhammadiyah Prof. Dr. Hamka, 2023)
Background: Microspores are small haploid spores that develop into the male gametophyte. Microsporocytes undergo meiotic division to form microspores. Microspores can be found in seedless and seed plants. The microspores in each flowering plant are different. This study aims to observe microspores on eggplant flowers. Method: Microspore observations were carried out on different flower bud sizes until the flower buds bloomed. Result: The results showed microspores in eggplant had different stages of development for each flower bud size. The stages of microspore development observed were Early uninucleate (Young microspore), Mid-uninucleate, Late uninucleate (Vacuolate microspore), early binucleate (Young bicellular pollen), mid-binucleate, and mature pollen. Conclusion: In eggplant microspore culture, anther length is a strong parameter to predict the stage of microspore development contained there in.